Generational Ownership Influence on Family Firm Performance in Indonesia - Mufidah, Eva; Setiawan, Heri Cahyo Bagus; Sabang, Yusmiaty (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study aims to determine the sustainability of generations in family firms in Indonesia. The effect of generational ownership on firm performance using ROA and ROE. Using agency theory and there are 522 observations and using unbalanced panel data in 2016-2020 in companies listed on the Indonesia Stock Exchange. Hypothesis testing uses unbalanced panel data regression tests. The test results for the 1st generation show that go1 has a positive and significant effect on firm performance using ROA and ROE. For the 2nd generation, it shows that go2 has a negative and significant effect on firm performance using ROA and ROE. While the 3rd generation shows that go3 does not have a significant effect on firm performance using ROA and ROE.